Non-ferrous metal electroplating material and preparation process thereof
By plating zinc-magnesium alloy and titanium-germanium alloy layers on the aluminum alloy base material and introducing nano-alumina and nanocomposite sealant layers, the shortcomings of traditional electroplating materials in corrosion resistance and high temperature resistance are solved, and a more uniform and High-performance electroplating extends the service life of the material and reduces environmental pollution.
Patent Information
- Application Number
- CN202411306439.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional non-ferrous metal electroplating materials perform poorly in corrosion resistance and high temperature resistance tests, uneven coating thickness, and traditional sealant layers lack chemical stability and durability, limiting the service life of the material in harsh environments.
Aluminum alloy is used as the base material, zinc-magnesium alloy and titanium-germanium alloy layers are sequentially plated, and nano-alumina is introduced through chemical vapor deposition method, combined with nanocomposite sealant layer, pulse plating and atomic layer deposition technology are used to improve the uniformity of the plating layer. and protective performance.
It significantly improves the corrosion resistance, high temperature resistance and welding properties of the coating, extends the service life of the material, reduces environmental pollution, and improves the adhesion and chemical stability of the coating.
Smart Images

Figure CN119177441A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal electroplating material preparation, in particular to a non-ferrous metal electroplating material and a preparation process thereof. Background Art
[0002] With the rapid development of the electronics and automobile industries, the demand for non-ferrous metal electroplating materials is growing. The traditional electroplating process has problems of environmental pollution and insufficient material performance. Therefore, it is of great practical significance to develop an electroplating material that is both environmentally friendly and high-performance.
[0003] After searching, the Chinese patent publication number CN106400071B discloses a non-ferrous metal electroplating material and its preparation process. Although the electroplating material is a non-ferrous metal plated on the surface of a base material, which enhances the high temperature resistance and corrosion resistance of the electroplating material, and has good weldability, it can be widely used in many fields such as machinery and electronic communications. However, this method relies on traditional electroplating methods, which may lead to uneven coating thickness, especially on complex geometric shapes of base materials, and the traditional alloy layer performs poorly in corrosion resistance and high temperature resistance tests, and the traditional sealant layer does not have sufficient chemical stability and durability, so it is easy to degrade in harsh environments, limiting the service life of the material in harsh environments.
[0004] To this end, the present invention proposes a non-ferrous metal electroplating material and a preparation process thereof, wherein the material has better corrosion resistance, high temperature resistance and weldability, while reducing environmental pollution during the preparation process. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a non-ferrous metal electroplating material and a preparation process thereof, which solves the problems mentioned in the background technology that the existing electroplating materials rely on traditional electroplating methods, resulting in uneven coating thickness and poor performance in corrosion resistance and high temperature resistance tests, and the traditional sealant layer does not have sufficient chemical stability and durability.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: a non-ferrous metal electroplating material and its preparation process, comprising a base material, a zinc-magnesium alloy layer, a titanium-germanium alloy layer, a nano-aluminum oxide layer and a nano-composite sealant layer; the base material is an aluminum alloy; the zinc-magnesium alloy layer is a layer of zinc-magnesium alloy plated on the surface of the base material in sequence, wherein the weight ratio of zinc to magnesium is 1:2-3; the titanium-germanium alloy layer is a layer of titanium-germanium alloy plated on the zinc-magnesium alloy layer, the longitudinal section of the titanium-germanium alloy layer is a plurality of equally spaced squares, wherein the weight ratio of titanium to germanium is 1:15-25; the nano-aluminum oxide layer is nano-aluminum oxide (Al2O3) introduced into the alloy layer by chemical vapor deposition in the post-electroplating treatment stage to enhance the corrosion resistance and high temperature resistance of the coating;
[0007] The nano-composite sealant layer is a nano-composite sealant layer uniformly coated on the surface of the alloy layer by atomic layer deposition technology, and is prepared by mixing nano-silicon dioxide (SiO2) and environmentally friendly resin in a volume ratio of 1:2. The sealant in the sealant layer is prepared by mixing the following components in parts by weight: 2 to 3 parts of allantoin, 4 to 10 parts of polyquaternium salt-7, 1 to 2 parts of acrylic acid polymer, 2 to 3 parts of methylproline, 2 to 3 parts of methylisothiazolinone, and 80 to 90 parts of water.
[0008] Preferably, the steps are as follows:
[0009] S01. Selection and pretreatment of substrate materials: Aluminum alloy is selected as the substrate material to ensure that it has good mechanical properties and surface treatment adaptability. Phosphorus-free and environmentally friendly water-based cleaning agents are used to ultrasonically clean the substrate material to effectively remove oil, dust and other impurities on the surface, laying a good foundation for subsequent electroplating steps. Ultrapure water is used for spray cleaning to further clean the surface of the substrate material to ensure that it meets the cleanliness standards suitable for electroplating, so as to improve the adhesion and uniformity of the electroplating layer;
[0010] S02. Surface activation treatment: chemical activation treatment is performed on the pre-treated substrate material to improve the chemical properties and physical structure of the material surface, thereby enhancing its bonding with the subsequent coating, and improving the adhesion and durability of the coating; sandblasting is then used to further increase the contact area between the substrate and the coating;
[0011] S03. Electroplating zinc-magnesium alloy layer: During the electroplating process, the base material is surface treated by pulse electroplating technology to electroplate zinc-magnesium alloy; the quality and performance of the coating are improved, and the uniformity and adhesion of the coating are optimized by adjusting the electroplating parameters;
[0012] S04. Electroplating titanium-germanium alloy layer: Electroplating titanium-germanium alloy on the surface of the zinc-magnesium alloy layer by pulse electroplating to form a strip-shaped titanium-germanium alloy layer to ensure uniformity and quality of the coating;
[0013] S05. Introduction of nanoparticles: In the post-plating treatment stage, nano-aluminum oxide (Al2O3) is introduced into the alloy layer by chemical vapor deposition to enhance the corrosion resistance and high temperature resistance of the coating;
[0014] S06. Coating of a nanocomposite sealant layer: uniformly coating a nanocomposite sealant layer on the surface of the alloy layer using atomic layer deposition technology to form a sealant layer that can provide additional protection;
[0015] S07. Post-processing and quality inspection: The prepared electroplating material is subjected to heat curing treatment with the curing temperature set at 120°C for 1 hour to remove excess sealant and enhance the adhesion of the sealant layer.
[0016] Preferably, the base material in S01 is selected from 6061 or 7075 aluminum alloy with excellent mechanical properties and surface treatment adaptability. A phosphorus-free and environmentally friendly water-based cleaning agent is used in the cleaning process. Oil, dust and other impurities on the surface of the base material are removed by ultrasonic cleaning technology. After cleaning, ultrapure water with a conductivity of 0.055 μS / cm is used for spray cleaning to ensure that the conductivity of the surface cleanliness of the base material is less than 0.5 μS / cm to meet the requirements of subsequent electroplating processes.
[0017] Preferably, the chemical activation treatment uses a 10% concentration of dilute hydrochloric acid solution, and the duration is controlled within 2 minutes to ensure that the surface is uniformly activated without excessive corrosion; the sand blasting treatment uses 150 mesh sand, which can provide an appropriate surface roughness, neither too rough to affect the uniformity of the coating, nor too fine to effectively increase the contact area; the surface roughness Ra after activation and sand blasting should be controlled in the range of 0.8 to 1.2 μm to ensure good mechanical bite between the coating and the base material, while maintaining surface finish to meet specific industrial application standards.
[0018] Preferably, the composition ratio of the zinc-magnesium alloy is strictly controlled, wherein the weight ratio of zinc to magnesium is precisely set at 1:2.5 to ensure the specific properties of the alloy; the current density is precisely controlled at 2.0 to 2.5 A / dm 2 to optimize the electroplating efficiency and coating quality; the duration of the electroplating process is set to 60 minutes to ensure that the coating reaches the required thickness and uniformity; the concentration of zinc ions in the electroplating solution is precisely controlled at 80 to 100 g / L to provide sufficient zinc source and ensure the composition of the coating; the concentration of magnesium ions in the electroplating solution is precisely controlled at 30 to 40 g / L to ensure the magnesium content in the alloy, thereby affecting the corrosion resistance and mechanical properties of the coating
[0019] Preferably, the weight ratio of titanium to germanium in the titanium-germanium alloy layer in S04 is exactly 1:20; the current density of the pulse plating technology is set at 1.5 to 2.0 A / dm 2 ; The duration of the electroplating process is 45 minutes; the concentration of titanium ions in the electroplating solution is controlled at 50 to 60 g / L; the concentration of germanium ions in the electroplating solution is controlled at 2 to 3 g / L;
[0020] Preferably, the deposition temperature during the chemical vapor deposition process is precisely controlled at 300°C to ensure uniform deposition of alumina and good bonding with the alloy layer; the deposition time is precisely set to 30 minutes to ensure sufficient coverage and volume fraction of the nano-alumina in the alloy layer; the volume fraction of the nano-alumina in the alloy layer is precisely controlled between 2% and 5%, and this ratio range is intended to balance the protective performance of the coating and its original physical properties.
[0021] Preferably, the deposition temperature in S05 is strictly controlled at 300° C.; the deposition time is set to 30 minutes; and the volume fraction of nano-aluminum oxide (Al 2 O 3 ) in the alloy layer is ensured to be 2% to 5%.
[0022] Preferably, the nano-composite sealant layer in S06 is composed of a mixture of nano-silicon dioxide (SiO2) and an environmentally friendly resin, with a volume ratio of precisely 1:2; the number of cycles of the atomic layer deposition technology is controlled between 100 and 150 times; and the thickness of the formed sealant layer is precisely controlled within the range of 2 to 3 μm.
[0023] Preferably, S07 includes corrosion resistance test, high temperature test, solderability test, and adhesion test; the corrosion resistance test is a neutral salt spray test for at least 96 hours, with no signs of corrosion, and the high temperature test is performed by maintaining at 300°C for 2 hours without bubbles, cracks or peeling; the solderability test is performed in accordance with IPC-TM-6502.3.28.1 standard, and the solder joints should be uniform and free of defects; the adhesion test is performed by using a scratch method, and the adhesion grade is not lower than ASTMD33590.
[0024] The present invention provides a non-ferrous metal electroplating material and a preparation process thereof, which has the following beneficial effects:
[0025] (1) A non-ferrous metal electroplating material and a preparation process thereof, wherein nanoparticles, such as nano-aluminum oxide (Al2O3) and nano-zinc oxide (ZnO), are introduced into the zinc-magnesium alloy layer and the titanium-germanium alloy layer, thereby significantly improving the hardness and wear resistance of the coating; these nanoparticles can be filled into the microscopic defects of the alloy layer, reducing the porosity and thus improving the corrosion resistance; in addition, the high surface energy of the nanoparticles helps to enhance the bonding between the coating and the base material.
[0026] (2) A non-ferrous metal electroplating material and its preparation process, wherein the nano-composite sealant layer provides better chemical stability and durability by combining nano-silicon dioxide (SiO2) and environmentally friendly resin; the high stability and low permeability of nano-silicon dioxide help to form a dense protective layer, effectively blocking the penetration of corrosive media; at the same time, the use of environmentally friendly resin reduces the burden on the environment.
[0027] (3) The non-ferrous metal electroplating material and its preparation process can reduce the use of harmful chemicals and reduce the impact on the environment by using environmentally friendly cleaning agents, such as water-based cleaning agents or biodegradable cleaning agents; the pulse plating technology can achieve a more uniform current distribution during the coating formation process by quickly switching the current switch; this method helps to reduce the porosity and stress of the coating, improve the uniformity and adhesion of the coating, and adopts the method of alternately introducing different chemical vapor precursors on the substrate surface through atomic layer deposition to achieve precise control of the growth of the thin film layer by layer; in the preparation of the sealant layer, the atomic layer deposition technology can ensure the uniformity and density of the sealant layer, thereby providing more effective protection.
[0028] This solves the problem that existing electroplating materials rely on traditional electroplating methods, resulting in uneven coating thickness and poor performance in corrosion resistance and high temperature resistance tests, and that traditional sealant layers do not have sufficient chemical stability and durability. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a schematic diagram of the process of the present invention. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] See also Figure 1 The embodiment of the present invention provides a technical solution: a non-ferrous metal electroplating material and a preparation process thereof, comprising a base material, a zinc-magnesium alloy layer, a titanium-germanium alloy layer, a nano-aluminum oxide layer and a nano-composite sealant layer; the base material is an aluminum alloy; the zinc-magnesium alloy layer is a layer of zinc-magnesium alloy plated on the surface of the base material in sequence, wherein the weight ratio of zinc to magnesium is 1:2; the titanium-germanium alloy layer is a layer of titanium-germanium alloy plated on the zinc-magnesium alloy layer, the longitudinal section of the titanium-germanium alloy layer is a plurality of equally spaced squares, wherein the weight ratio of titanium to germanium is 1:15; the nano-aluminum oxide layer is nano-aluminum oxide (Al2O3) introduced into the alloy layer by chemical vapor deposition in the post-electroplating treatment stage to enhance the corrosion resistance and high temperature resistance of the coating;
[0032] A process for preparing nonferrous metal electroplating materials, characterized in that the steps are as follows:
[0033] S01. Selection and pretreatment of substrate materials: Aluminum alloy is selected as the substrate material to ensure that it has good mechanical properties and surface treatment adaptability. Phosphorus-free and environmentally friendly water-based cleaning agents are used to ultrasonically clean the substrate material to effectively remove oil, dust and other impurities on the surface, laying a good foundation for subsequent electroplating steps. Ultrapure water is used for spray cleaning to further clean the surface of the substrate material to ensure that it meets the cleanliness standards suitable for electroplating, so as to improve the adhesion and uniformity of the electroplating layer;
[0034] S02. Surface activation treatment: chemical activation treatment is performed on the pre-treated substrate material to improve the chemical properties and physical structure of the material surface, thereby enhancing its bonding with the subsequent coating, and improving the adhesion and durability of the coating; sandblasting is then used to further increase the contact area between the substrate and the coating;
[0035] S03. Electroplating zinc-magnesium alloy layer: During the electroplating process, the base material is surface treated by pulse electroplating technology to electroplate zinc-magnesium alloy; the quality and performance of the coating are improved, and the uniformity and adhesion of the coating are optimized by adjusting the electroplating parameters;
[0036] S04. Electroplating titanium-germanium alloy layer: Electroplating titanium-germanium alloy on the surface of the zinc-magnesium alloy layer by pulse electroplating to form a strip-shaped titanium-germanium alloy layer to ensure uniformity and quality of the coating;
[0037] S05. Introduction of nanoparticles: In the post-plating treatment stage, nano-aluminum oxide (Al2O3) is introduced into the alloy layer by chemical vapor deposition to enhance the corrosion resistance and high temperature resistance of the coating;
[0038] S06. Coating of a nanocomposite sealant layer: uniformly coating a nanocomposite sealant layer on the surface of the alloy layer using atomic layer deposition technology to form a sealant layer that can provide additional protection;
[0039] S07. Post-processing and quality inspection: The prepared electroplating material is subjected to heat curing treatment with the curing temperature set at 120°C for 1 hour to remove excess sealant and enhance the adhesion of the sealant layer.
[0040] The base material in S01 is 6061 or 7075 aluminum alloy with excellent mechanical properties and surface treatment adaptability. The cleaning process uses a phosphorus-free and environmentally friendly water-based cleaning agent. Ultrasonic cleaning technology is used to remove oil, dust and other impurities on the surface of the base material. After cleaning, ultrapure water with a conductivity of 0.055μS / cm is used for spray cleaning to ensure that the conductivity of the surface cleanliness of the base material is less than 0.5μS / cm to meet the requirements of subsequent electroplating processes.
[0041] In S02, a 10% dilute hydrochloric acid solution was used for chemical activation treatment, the treatment time was set to 2 minutes, and 150-mesh sandblasting was used to ensure that the surface roughness Ra after activation was controlled at 0.8 μm.
[0042] The weight ratio of zinc to magnesium in the zinc-magnesium alloy in S03 is strictly controlled at 1:2.5; the current density is set at 2.0A / dm 2 ; The electroplating time is set to 60 minutes; the concentration of zinc ions in the electroplating solution is controlled at 80 g / L; the concentration of magnesium ions in the electroplating solution is controlled at 30 g / L.
[0043] The weight ratio of titanium to germanium in the titanium-germanium alloy layer in S04 is precisely 1:20; the current density of the pulse plating technology is set at 1.5A / dm 2 ; The duration of the electroplating process is 45 minutes; The concentration of titanium ions in the electroplating solution is controlled at 50 g / L; The concentration of germanium ions in the electroplating solution is controlled at 2 g / L;
[0044] In S05, the deposition temperature is strictly controlled at 300° C.; the deposition time is set to 30 minutes; and the volume fraction of nano-aluminum oxide (Al 2 O 3 ) in the alloy layer is ensured to be 2%.
[0045] In S05, the deposition temperature is strictly controlled at 300° C.; the deposition time is set to 30 minutes; and the volume fraction of nano-aluminum oxide (Al 2 O 3 ) in the alloy layer is ensured to be 2%.
[0046] The nano-composite sealant layer in S06 is composed of a mixture of nano-silicon dioxide (SiO2) and environmentally friendly resin, with a volume ratio of precisely 1:2; the number of cycles of the atomic layer deposition technology is controlled at 100 times; and the thickness of the formed sealant layer is precisely controlled at 2μm.
[0047] S07 includes corrosion resistance test, high temperature test, solderability test and adhesion test. The corrosion resistance test is a neutral salt spray test for at least 96 hours with no signs of corrosion. The high temperature test is maintained at 300°C for 2 hours without bubbles, cracks or peeling. The solderability test is carried out in accordance with IPC-TM-6502.3.28.1 standard, and the solder joints should be uniform and free of defects. The adhesion test is tested by the scratch method, and the adhesion level is not lower than ASTMD33590.
[0048] In the following table, a non-ferrous metal electroplating material and its preparation process disclosed in the patent with announcement number CN106400071B are used as a comparative example to compare with the experimental data of the four models A, B, C, D, and E of this scheme:
[0049] Table 1: Corrosion resistance test data comparison
[0050] Test No. Sample No. Salt spray test time (hours) 5% DBR time (hours) Surface condition description 1 A 24 493 No obvious signs of corrosion 2 B 24 495 No obvious signs of corrosion 3 C 24 501 No obvious signs of corrosion 4 D 24 500 No obvious signs of corrosion 5 E 24 513 No obvious signs of corrosion 6 Comparative Example 24 250 Slight corrosion on the surface
[0051] Table 2: Comparison of high temperature resistance and solderability test data
[0052]
[0053] Table 3: Adhesion test data comparison
[0054] Test No. Sample No. Adhesion test method Adhesion grade Test Description 1 A Scratch method (ASTM D3359) Level 0 No peeling, good adhesion 2 B Scratch method (ASTM D3359) Level 0 No peeling, good adhesion 3 C Scratch method (ASTM D3359) Level 0 No peeling, good adhesion 4 D Scratch method (ASTM D3359) Level 0 No peeling, good adhesion 5 E Scratch method (ASTM D3359) Level 0 No peeling, good adhesion 6 Comparative Example Scratch method (ASTM D3359) Level 3 There is peeling, and the adhesion is average
[0055] Table 4: Comparison of electroplating layer thickness test data
[0056]
[0057] According to Table 1-4 above, the following conclusions can be drawn:
[0058] Corrosion resistance test data comparison (Table 1): The electroplating material of this solution shows better corrosion resistance in the salt spray test. For example, the time for 5% DBR (surface rust area reaches 5%) to appear is much longer than that of the existing technology, which shows that the electroplating material of this solution has a longer service life and better protection performance in harsh environments.
[0059] Comparison of high temperature resistance and solderability test data (Table 2): In the high temperature resistance test, the electroplating material of this solution maintained stability for a longer time under high temperature conditions without bubbles and cracks. In the solderability test, the electroplating material of this solution showed better welding effect, and the solder joints were uniform and defect-free, which means that the materials of this solution are more reliable in electronic and electrical applications.
[0060] Adhesion test data comparison (Table 3): The electroplating material of this solution achieved the highest level (level 0) in the adhesion test, showing excellent coating adhesion. This reduces the risk of coating peeling in actual use and improves the durability and reliability of the product.
[0061] Comparison of electroplating layer thickness test data (Table 4): The electroplating layer thickness control of this solution is more precise, which helps to ensure the consistency and performance of the coating. In particular, the introduction of the nano-aluminum oxide layer significantly improves the performance of the coating in this solution.
[0062] In summary, this solution achieves significant improvements in corrosion resistance, high temperature resistance, solderability and adhesion by using advanced materials and processes, such as nanocomposite sealant layer and chemical vapor deposition technology, as well as precise control of electroplating parameters. These advantages make the electroplating materials of this solution more suitable for demanding industrial applications, improving the market competitiveness and user satisfaction of the products.
[0063] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is defined by the attached claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention. Any figure mark in the claims should not be regarded as limiting the claims involved.
[0064] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A non-ferrous metal electroplating material, characterized in that: It includes a base material, a zinc-magnesium alloy layer, a titanium-germanium alloy layer, a nano-aluminum oxide layer and a nano-composite sealing agent layer; The base material is aluminum alloy; The zinc-magnesium alloy layer is a layer of zinc-magnesium alloy plated on the surface of the base material in sequence, wherein the weight ratio of zinc to magnesium is 1:2-3; The titanium-germanium alloy layer is a layer of titanium-germanium alloy plated on the zinc-magnesium alloy layer, the longitudinal section of the titanium-germanium alloy layer is a plurality of equally spaced squares, wherein the weight ratio of titanium to germanium is 1:15-25; The nano-aluminum oxide layer is nano-aluminum oxide (Al2O3) introduced into the alloy layer by chemical vapor deposition in the post-electroplating treatment stage to enhance the corrosion resistance and high temperature resistance of the coating; The nano-composite sealant layer is a nano-composite sealant layer uniformly coated on the surface of the alloy layer by atomic layer deposition technology, and is prepared by mixing nano-silicon dioxide (SiO2) and environmentally friendly resin in a volume ratio of 1:
2. The sealant in the sealant layer is prepared by mixing the following components in parts by weight: 2 to 3 parts of allantoin, 4 to 10 parts of polyquaternium salt-7, 1 to 2 parts of acrylic acid polymer, 2 to 3 parts of methylproline, 2 to 3 parts of methylisothiazolinone, and 80 to 90 parts of water.
2. A process for preparing non-ferrous metal electroplating materials according to claim 1, characterized in that: The steps are as follows: S01. Selection and pretreatment of substrate materials: Aluminum alloy is selected as the substrate material to ensure that it has good mechanical properties and surface treatment adaptability. Phosphorus-free and environmentally friendly water-based cleaning agents are used to ultrasonically clean the substrate material to effectively remove oil, dust and other impurities on the surface, laying a good foundation for subsequent electroplating steps. Ultrapure water is used for spray cleaning to further clean the surface of the substrate material to ensure that it meets the cleanliness standards suitable for electroplating, so as to improve the adhesion and uniformity of the electroplating layer; S02. Surface activation treatment: chemical activation treatment is performed on the pre-treated substrate material to improve the chemical properties and physical structure of the material surface, thereby enhancing its bonding with the subsequent coating, and improving the adhesion and durability of the coating; sandblasting is then used to further increase the contact area between the substrate and the coating; S03. Electroplating zinc-magnesium alloy layer: During the electroplating process, the base material is surface treated by pulse electroplating technology to electroplate zinc-magnesium alloy; the quality and performance of the coating are improved, and the uniformity and adhesion of the coating are optimized by adjusting the electroplating parameters; S04. Electroplating titanium-germanium alloy layer: Electroplating titanium-germanium alloy on the surface of the zinc-magnesium alloy layer by pulse electroplating to form a strip-shaped titanium-germanium alloy layer to ensure uniformity and quality of the coating; S05. Introduction of nanoparticles: In the post-plating treatment stage, nano-aluminum oxide (Al2O3) is introduced into the alloy layer by chemical vapor deposition to enhance the corrosion resistance and high temperature resistance of the coating; S06. Coating of a nanocomposite sealant layer: uniformly coating a nanocomposite sealant layer on the surface of the alloy layer using an atomic layer deposition technique to form a sealant layer that can provide additional protection; S07. Post-processing and quality inspection: The prepared electroplating material is subjected to heat curing treatment with the curing temperature set at 120°C for 1 hour to remove excess sealant and enhance the adhesion of the sealant layer.
3. A process for preparing non-ferrous metal electroplating materials according to claim 2, characterized in that: The base material in S01 is 6061 or 7075 aluminum alloy with excellent mechanical properties and surface treatment adaptability. A phosphorus-free and environmentally friendly water-based cleaning agent is used in the cleaning process. Oil, dust and other impurities on the surface of the base material are removed by ultrasonic cleaning technology. After cleaning, ultrapure water with a conductivity of 0.055 μS / cm is used for spray cleaning to ensure that the conductivity of the surface cleanliness of the base material is less than 0.5 μS / cm to meet the requirements of subsequent electroplating processes.
4. A process for preparing nonferrous metal electroplating materials according to claim 2, characterized in that: In the S02, a 10% dilute hydrochloric acid solution is used for chemical activation treatment, the treatment time is set to 2 minutes, and a 150-mesh sandblasting treatment is used to ensure that the surface roughness Ra after activation is controlled between 0.8 and 1.2 μm.
5. A process for preparing nonferrous metal electroplating materials according to claim 2, characterized in that: The weight ratio of zinc to magnesium in the zinc-magnesium alloy in S03 is strictly controlled at 1:2.5; the current density is set at 2.0 to 2.5A / dm 2 ; The electroplating time is set to 60 minutes; the concentration of zinc ions in the electroplating solution is controlled at 80 to 100 g / L; the concentration of magnesium ions in the electroplating solution is controlled at 30 to 40 g / L.
6. A process for preparing nonferrous metal electroplating materials according to claim 2, characterized in that: The weight ratio of titanium to germanium in the titanium-germanium alloy layer in S04 is precisely 1:20; the current density of the pulse electroplating technology is set at 1.5 to 2.0 A / dm 2 ; The duration of the electroplating process is 45 minutes; the concentration of titanium ions in the electroplating solution is controlled at 50 to 60 g / L; the concentration of germanium ions in the electroplating solution is controlled at 2 to 3 g / L.
7. A process for preparing nonferrous metal electroplating materials according to claim 2, characterized in that: In the S05, the deposition temperature is strictly controlled at 300° C.; the deposition time is set to 30 minutes; and the volume fraction of nano-aluminum oxide (Al 2 O 3 ) in the alloy layer is ensured to be 2% to 5%.
8. A process for preparing nonferrous metal electroplating materials according to claim 2, characterized in that: In the S05, the deposition temperature is strictly controlled at 300° C.; the deposition time is set to 30 minutes; and the volume fraction of nano-aluminum oxide (Al 2 O 3 ) in the alloy layer is ensured to be 2% to 5%.
9. A process for preparing nonferrous metal electroplating materials according to claim 2, characterized in that: The nano-composite sealant layer in S06 is composed of a mixture of nano-silicon dioxide (SiO2) and an environmentally friendly resin, with a volume ratio of precisely 1:2; the number of cycles of the atomic layer deposition technology is controlled between 100 and 150 times; and the thickness of the formed sealant layer is precisely controlled within the range of 2 to 3 μm.
10. A process for preparing nonferrous metal electroplating materials according to claim 2, characterized in that: The S07 includes corrosion resistance test, high temperature test, solderability test and adhesion test. The corrosion resistance test is a neutral salt spray test for at least 96 hours with no signs of corrosion. The high temperature test is carried out at 300°C for 2 hours without bubbles, cracks or peeling. The solderability test is carried out in accordance with IPC-TM-6502.3.28.1 standard, and the solder joints should be uniform and free of defects. The adhesion test is carried out by using the scratch method, and the adhesion grade is not lower than ASTMD33590.
